The Impact of Online Interaction on User Loyalty in Social Commerce through the Mediation of Shopping Value - Indra Akbar; Sofyan Sofyan; Ismail Ismail (International Journal of Management Science and Information Technology, 2026)
This research investigates how online interactions influence user loyalty in social commerce, focusing on shopping value as a mediating factor. Utilizing a quantitative approach through Structural Equation Modeling-Partial Least Square (SEM-PLS), data were gathered from 150 respondents who engaged in transactions via platforms like TikTok Shop, Shopee Live, Instagram Shop, and Facebook Marketplace. An online questionnaire employing a five-point Likert scale facilitated data collection. The findings reveal a significant positive relationship between online interactions and both shopping value and user loyalty. Furthermore, shopping value not only impacts loyalty but also serves as a partial mediator linking online interactions to user loyalty. These results indicate that effective digital interactions, marked by prompt responses and clear communication, enhance users' perceived value during transactions. This, in turn, fosters a greater likelihood of repeated use of the platforms. All hypotheses were validated through bootstrapping analysis, meeting the required statistical significance. The study underscores that user loyalty is shaped not only by direct interactions but also by the value experiences that emerge during shopping activities.